Pemberdayaan Ekonomi Masyarakat Kelurahan Kastela Kota Ternate - Marwan, Marwan (Abdi Masyarakat, 2022)
The purpose of this program is to actualize one of the elements of the Tri Dharma of Higher Education, namely community service and to assist the community in increasing community productivity in the Kastela village. The method used is focus group discussion (FGD). The result is that the community and the management group will hold a meeting to discuss the complete arrangement of the Kastela beach tourism area. Among them will be arrangement of objects that will serve as an attraction for visitors. For this reason, the Kastela beach as the main object will be arranged to be able to encourage visitors' interest and be interested in always visiting. Among them are 1) The parking area will be prepared and arranged so that it can give the impression of being comfortable and safe for visitors. For this purpose, special land will be prepared within the tourist attraction area; 2) Gardening will be done to create a beautiful environment, fresher air, and trees and flowers that can add joy to visitors; 3) Stalls selling various culinary delights will also be arranged and their skills will be improved in processing various traditional foods. Likewise with the ability to provide services to visitors who come.